Novel fusants of two and three clostridia for enhanced green production of biobutanol. Issue 8 (14th September 2021) - Mohtasebi, Banafsheh; Maki, Miranda; Qin, Wensheng; Dahman, Yaser
Abstract: The objective of the present study is to improve biobutanol production by utilizing renewable resources of agriculture residues (i.e. wheat straws) in simultaneous saccharification and fermentation (SSF). Three strains of anaerobic gram-positive clostridia ( Clostridium beijerinckii, Clostridium thermocellum, and Thermoanaerobacterium saccharolyticum ) were fused through a protoplast fusion technique. Results show that protoplast fusion of thermophilic and mesophilic clostridia led to improved thermostability in a fermentation medium at 45 °C. This represents the optimum temperature for enzymatic hydrolysis. Results also show that the fused strain produced essential hydrolysis enzymes, which eliminated the need to add any enzymes during the hydrolysis step. Furthermore, results in the present study demonstrate that the fused culture of bacteria was able to tolerate the elevated concentration of acetone, butanol, and ethanol during production, which resulted in higher biobutanol production of 13.8 g/L. This study includes a comparison with the co-culture as a benchmark to account for the effects of protoplast fusion.